A STUDY ON PATTERN OF PARASUICIDE (Journal of Forensic Medicine & Toxicology, 2011)
Suicide, the desperate last resort to end the agony, actually ends up in loss of life. Suicide is a social taboo often frowned upon, but the truth remains that it’s incidence is on the rise .A precious life is lost when it succumbs to hopelessness around it, it leaves a question mark on what could have lead to this extent of anguish, and to what extent a person might have struggled between hope and despair, before ending his life. Suicide which is mostly the result of psychiatric illness is an underreported entity, and represents just tip of prevailing distress in the society. Parasuicide or attempted suicide is a better indicator of mental health of society, attempted suicide being 8-10 times higher than suicide.
Keywords: Parasucide; Suicide; Pattern of parasuicide